Follicle Stimulating Hormone and Anti-Müllerian Hormone among Fertile and Infertile Women in Ile-Ife, Nigeria: Is there A Difference? - Okunola, Temitope (Int J Fertil Steril, 2017)
BACKGROUND: Reduced ovarian reserve predicts poor ovarian response and poor suc- cess rates in infertile women who undergo assisted reproductive technology (ART). Ovarian reserve also decreases with age but the rate of decline varies from one woman to another. This study aims to detect differences in ovarian reserve as measured by basal serum follicle stimulating hormone (FSH) and anti-Müllerian hormone (AMH) between a matched cohort of fertile and infertile regularly menstruating women, 18-45 years of age. MATERIALS AND METHODS: This case-control study involved 64 fertile and 64 subfertile women matched by age at recruitment. Peripheral blood samples were taken from the women recruited from the Gynecological and Outpatient Clinics of Obafemi Awolowo University Teaching Hospital, Ile-Ife, Nigeria. Serum FSH and AMH were quantified using ELISA at the Metabolic Research Laboratory of LAUTECH Teaching Hospital, Ogbomoso, Nigeria. RESULTS: A significant difference existed in the mean FSH of fertile (6.97 ± 3.34) and infertile (13.34 ± 5.24, P=0.013) women. We observed a significant difference in AMH between fertile (2.71 ± 1.91) and infertile (1.60 ± 2.51, P=0.029) women. There was a negative correlation between FSH and AMH in both fertile (r=-0.311, P=0.01) and infertile (r=-0.374, P=0.002) women. CONCLUSION: The difference in ovarian reserve observed in this study suggests that reduced ovarian reserve in regularly menstruating women may be associated with early ovarian ageing or subfertility.